2017
DOI: 10.1515/jvetres-2017-0049
|View full text |Cite
|
Sign up to set email alerts
|

Hoof quality of Anglo-Arabian and Haflinger horses

Abstract: IntroductionFoot quality is essential to the horse’s movement. The barefoot approach favours the animal’s welfare. Environment and selection determine hoof characteristics.Material and MethodsHoof characteristics of eight Anglo-Arabian (AA) and nine Haflinger (HA) horses were studied. After a preliminary visual analysis of feet, nail samples were collected after trimming for physico-chemical analysis. The parameters were submitted to analysis of variance. A principal component analysis and a Pearson correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…For example, Mg levels obtained in this study were 181 ± 98 µg/g, while de Souza et al (30) reported different Mg values from the wall (960 ± 631 ppm) and the frog (1,389 ± 768 ppm). Similarly, Tocci et al (21) reported Mg values for the hoof wall of 373 ± 33 ppm and 255 ± 38 ppm for the sole. These discrepancies can be attributed to the fact that mineral contents will vary depending on the hoof sampling area, and therefore, during sampling, it is important to use the same sites in order to be comparable in the same study.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, Mg levels obtained in this study were 181 ± 98 µg/g, while de Souza et al (30) reported different Mg values from the wall (960 ± 631 ppm) and the frog (1,389 ± 768 ppm). Similarly, Tocci et al (21) reported Mg values for the hoof wall of 373 ± 33 ppm and 255 ± 38 ppm for the sole. These discrepancies can be attributed to the fact that mineral contents will vary depending on the hoof sampling area, and therefore, during sampling, it is important to use the same sites in order to be comparable in the same study.…”
Section: Discussionmentioning
confidence: 80%
“…The hoof structure is very important for horse welfare and performance, and therefore, results obtained in this study seek to expand the knowledge and existing values on the mineral contents of horses' hooves, in addition to tensile strength values (20)(21)(22). Until today, studies on this topic from horses in Latin America are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The average wool production ranges from 2.5 kg (rams) to 1.5 kg (sheep). Pomarancina wool is a coarse wool that is suitable for making mattresses [25].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies emphasize the health benefits of unshod horse hooves [21][22][23][24], with an increasing number of horse owners choosing barefoot options [25,26]. To the best of our knowledge, sole thickness in hooves of domesticated, barefoot-kept horses walking over hard, artificial environments has not been reported in equine veterinary literature.…”
Section: Introductionmentioning
confidence: 99%